Effect of broiler litter supplementation on reproductive performance of West African dwarf sheep (2015)
Four low cost feed samples were formulated using 0, 25, 50 and 75% levels of broiler litter processed into feed along with other feed ingredients. Sixteen (16) primiparous West African Dwarf (WAD) ewes aged between twelve and eighteen months old were dewormed using Ivermectin and dipped against ticks and fleas using diazintol. Oestrus was artificially synchronized in all the ewes using 1ml of Prostaglandin - 2Fα administered intramuscularly, the animals were mated with rams of known fertility and lineage bred. Ewes were evaluated in a pregnancy trial while the lambs born were evaluated in a pre-weaning growth trial. All the ewes were weighed before conception and bimonthly thereafter until parturition. The parameters studied were weight at mating, weight before and after parturition, weight changes during pregnancy, weight changes in lactation and nursing, lambs birth weights and daily weight of lambs, dam's weight at weaning and gestation length. Results obtained showed weight at mating, weight before mating, weight at parturition, gestation length, weight gain in pregnancy, weight change in lactation and nursing, lambs birth weights and daily weight gain of lambs were significantly affected (p<0.05) while dam's weight at weaning and lambs' weaning weight were not affected (p>0.05). Results of this study indicate that inclusion of broiler litter up to 50% in feed mixtures of ewes has no deleterious effect on the performance and health status of ewes during pregnancy and lactation.